TRADITIONAL ISLAM IN JAVANESE SOCIETY: The Roles of Kyai and Pesantren in Preserving Islamic Tradition and Negotiating Modernity (JOURNAL OF INDONESIAN ISLAM, 2012)
The debate on the notion of identity of the traditional Islam in the Javanese society is often related to pesantren and kyai. These are the sub-cultural entities that have contributed to the shaping and building the identity of the Javanese Muslims. This paper explores the following key issues: (1) In what ways the collective identity of the Javanese Muslims is constructed in such a multicultural society? (2) What are the roles of the pesantren and kyais in such a process. The paper argues that the pesantren communities perceive themselves as the defending power of traditional Islam, the fact that would imply logically that there is a sort of cultural confrontation between the traditionalists and the modernists. The paper will delve into this polarity in the context of the role of pesantren and kyai and how these sub-cultural entities negotiate both with the opposing sub-culture –the modernist that is- and with modernity.